Pengembangan Fasilitas Pendukung Desa Wisata Jamu Kiringan di Kabupaten Bantul - Floriberta Binarti; Juan Ferary Samosir; Wahyu Hanavira; Gegerius Deri; Amos Setiadi; Apridus Kefas Lapenangga (Jurnal Atma Inovasia, 2026)
The provision of supporting tourism facilities has become an urgent need for Kiringan Herbal Tourism Village, which has been officially developed since 2016. In addition to basic amenities such as parking areas, herbal shops, integrated toilets and meeting spaces, and a family medicinal plant garden (TOGA), the site’s natural assets—dense vegetation and a fast-flowing river—offer strong potential for nature- and river-based herbal tourism. The introduction of viewing platforms, a river dock, and a rafting storage facility is proposed to strengthen the integrated herbal and ecotourism character of Kiringan Hamlet. A therapeutic design approach is adopted to enhance the herbal tourism experience by fostering health-oriented, tranquil, and holistic restorative activities. The community-owned site is envisioned as a healing environment, combining permanent and semi-permanent structures arranged with high environmental sensitivity. Design strategies emphasize minimal tree cutting, maximized visual connections to the river, vegetation, and TOGA garden, and the preservation of distinctive natural soundscapes that reinforce the site’s therapeutic identity.